2015
DOI: 10.1590/0004-282x20150020
|View full text |Cite
|
Sign up to set email alerts
|

Surgical exposure of the internal auditory canal through the retrosigmoid approach with semicircular canals anatomical preservation

Abstract: Objective Evaluate the feasibility of an adequate exposure with anatomical preservation of labyrinth structures through retrosigmoid transmeatal approach (RSA) in surgeries for resection of acoustic neuromas/vestibular schwannomas (VS). Method Thirty patients underwent surgical resection and were preoperatively evaluated with fine slice high definition CT scans and 3D-MRI volumetric reconstructions. Extension of internal auditory canal (IAC) opening during surgery was measured using 3 mm right-angle calibrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…36 Symptoms as manifestation of nerves involvement help us also to chose the treatment. Good hearing threshold and vestibular function preservation are findings often present in arachnoid cyst, this suggests that a middle temporal fosse approach 37 or a retrosigmoid one 38 can be the good option to preserve the nerve functions. The endoscopic approach 19,39 would be the best choice but not all surgeons are comfortable with it.…”
Section: Discussionmentioning
confidence: 96%
“…36 Symptoms as manifestation of nerves involvement help us also to chose the treatment. Good hearing threshold and vestibular function preservation are findings often present in arachnoid cyst, this suggests that a middle temporal fosse approach 37 or a retrosigmoid one 38 can be the good option to preserve the nerve functions. The endoscopic approach 19,39 would be the best choice but not all surgeons are comfortable with it.…”
Section: Discussionmentioning
confidence: 96%
“…as previously described. 9 Patients were included in the study if they had diagnosis of VS confirmed by pathological examination and the surgical video was available for analysis. Precise intraoperative facial nerve identification at the brainstem and internal auditory canal by electro-stimulation with 2.0 mA and a minimum of 1-year follow-up were requirements of inclusion in this study.…”
Section: Methods Populationmentioning
confidence: 99%
“…However, various studies reported potential usefulness and thereby corroborate an unmet clinical need for accurate and precise instrument localization in neurotologic surgery (5). Based on intraoperative judgement by the operating surgeon potential usefulness during surgical access creation to the petrous apex (7,11,13,27,52) and to the internal auditory canal (16,27,43,52), resection of (pseudo)neoplasms (27,52,53), congenital bony aural atresia surgery (12), cochlear implantation (6, 9, 10) and revision surgery (27) was reported. In the presented study, during the removal of the facial nerve schwannoma, the imageguidance system was subjectively judged useful by the operating surgeon, mostly to delineate the facial nerve and determine the instrument's proximity to the dura.…”
Section: Usefulness Assessmentmentioning
confidence: 93%
“…The technology was reported as useful for identifying anatomy and pathology in (pseudo)neoplasm resection (7,8,13), cochlear implantation (9,10), congenital aural atresia (12), and auricular implant (14) surgery but no significant effects on safety or efficacy were demonstrated. Other attempts have suggested potential usefulness in otologic, petrous apex, and internal auditory canal surgery (6,11,15,16). The persistent lack of proven effects and absence in routine use, however, indicate that the clinically available freehand image-guidance systems still do not meet the needs of neurotologic surgery, most importantly the need for sub-half-millimeter localization accuracy and precision.…”
Section: Introductionmentioning
confidence: 99%